2017
DOI: 10.1038/hgv.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

The smallest de novo 20q11.2 microdeletion causing intellectual disability and dysmorphic features

Abstract: The 20q11.2 microdeletion is a rare chromosomal aberration characterized by intellectual disability (ID), motor developmental delay, neonatal feeding problems, and facial dysmorphism. Here, a 2-year- and 6-month-old Japanese girl with a 1.2 Mb microdeletion of 20q11.2 showed ID, motor developmental delay, and distinctive facial features without feeding problems. The deleted region was identified by array-based comparative genomic hybridization and is the smallest reported for a 20q11.2 microdeletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…A case with a 7.5 Mb 20q13.2-q13.33 deletion was reported that presented pre-and post-natal growth retardation, with absent speech, intellectual disability, hypotonia, and a unilateral cleft lip [32]. Another reported case had a de novo 20q11.2 microdeletion, measuring 1.2 Mb, which resulted in intellectual disability and dysmorphic features [33]. In our group we had a special situation, more precisely two consecutive pregnancies of the same woman, where the 20q deletion was identified, with diameters of 18.4 M and 19.5 M. In both pregnancies, microarray excluded the deletions, and two normal children were born.…”
Section: Discussionmentioning
confidence: 99%
“…A case with a 7.5 Mb 20q13.2-q13.33 deletion was reported that presented pre-and post-natal growth retardation, with absent speech, intellectual disability, hypotonia, and a unilateral cleft lip [32]. Another reported case had a de novo 20q11.2 microdeletion, measuring 1.2 Mb, which resulted in intellectual disability and dysmorphic features [33]. In our group we had a special situation, more precisely two consecutive pregnancies of the same woman, where the 20q deletion was identified, with diameters of 18.4 M and 19.5 M. In both pregnancies, microarray excluded the deletions, and two normal children were born.…”
Section: Discussionmentioning
confidence: 99%
“…These authors proposed the 20q11.2 microdeletion syndrome to be a new contiguous gene deletion syndrome with a recognizable phenotype; the researchers identified a 1.62 Mb minimal critical region, encompassing three genes ( GDF5 , EPB41L1 , and SAMHD1 ), as strong candidates to account for several phenotypic features. Hanafusa et al (2017) reported the smallest de novo 20q11.2 microdeletion (1.2 Mb) in 2‐year‐ and 6‐month‐old Japanese girls with intellectual disability, motor developmental delay, and facial features without feeding problems. This deletion did not overlap the minimal critical genomic region described by Jedraszak et al, encompassing the GDF5 , EPB41L1 , and SAMHD1 candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Along with numerical chromosome anomalies, such as mosaicism, structural anomalies of the chromosome 20, including ring chromosome [45], deletion of the short arm [46], microduplication within the short arm [47], and microdeleletion of the long arm [48], have also been associated with alterations in several body systems and functions as well as neurocognitive difficulties and neuropsychiatric features. Commonly reported behavioral manifestations include developmental delay, intellectual disability, sensory processing disorder, poor motor coordination, impaired speech and executive abilities, apathy or hyperactivity, loss of social skills and poor emotional regulation, obsessive behavior, psychosis, and autistic features.…”
Section: Discussionmentioning
confidence: 99%